PEMBERDAYAAN MASYARAKAT DESA WISATA SUKUNAN UNTUK MENINGKATKAN KEWIRAUSAHAAN MELALUI PENDAMPINGAN PENGOLAHAN MAKANAN RINGAN DIGAMPING, SLEMAN - Aznam, Azis Fitri Profita; Dewi, Winda Rosita; Nurhayati, Neneng (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
Sukunan Village in Sleman has successfully developed into an environmentally friendly tourism village with the potential for local culinary products, such as banana-based snacks, to support the village economy. Through a Community Service Program (PkM), residents received training in processing light snacks, namely Pisang Aroma and Risol Mayo, as well as plating and packaging techniques to enhance the culinary appeal of Sukunan as a tourist destination. The program implementation included counseling on local culinary potential, training in processing techniques, hands-on practice with mentoring, and product evaluation. The training results improved participants' skills in producing high-quality products. This program is expected to further develop Sukunan's culinary potential, increase community income, and support sustainable tourism based on local wisdom.